2017
DOI: 10.1038/s41598-017-03977-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong sub-seasonal wintertime cooling over East Asia and Northern Europe associated with super El Niño events

Abstract: East Asia experienced a record-breaking cold event during the 2015/16 boreal winter, with pronounced impacts on livelihood in the region. We find that this large-scale cold spell can be attributed to the concurrent super El Niño event in the tropical Pacific. Our analysis reveals that all super El Niño winters (1982/83, 1997/98, and 2015/16) were accompanied by a rapid sub-seasonal North Atlantic Oscillation (NAO)/Arctic Oscillation (AO) phase reversal from a positive to a negative state during early January, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 43 publications
3
37
0
1
Order By: Relevance
“…Geng et al . () found that strong El Niño events (anomaly of 2 K or more) in observations are associated with a shift to a negative NAO in January and cooling in northern Europe and East Asia in the absence of significant perturbation of the stratospheric polar vortex. However, Toniazzo and Scaife () and Hardiman et al .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Geng et al . () found that strong El Niño events (anomaly of 2 K or more) in observations are associated with a shift to a negative NAO in January and cooling in northern Europe and East Asia in the absence of significant perturbation of the stratospheric polar vortex. However, Toniazzo and Scaife () and Hardiman et al .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is reported that climate change is "perhaps the single greatest challenge confronting the Asia-Pacific region, and its more than 4 billion people [17]". A recent study has indicated that SH intensity is enhancing [18], favoring a southward intrusion of cold air towards East Asia [19], though global warming trends are also expected to affect the SH. The warming trend over the period 1901-2009 is particularly strong for the semiarid area of Asia, with an increase of 2.4 • C during the cold season between November and March.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the January 2008 cold event induced long‐lasting snowstorms with severe icy conditions in southern China (Lu et al, ; Wen et al, ; Zhou et al, ). In late January 2016, a strong cold event hit a large part of East Asia (Cheung et al, ; Geng et al, ; Song & Wu, ), setting the new lowest temperature record and causing the death of people in lower latitude East Asian regions (http://edition.cnn.com/2016/01/25/asia/asia-cold-weather-travel-disruption/index.html). It is important to understand what the factors and processes are of intraseasonal variations during boreal winter over East Asia for improving the prediction of cold events and reducing the related loss.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the January 2008 cold event induced long-lasting snowstorms with severe icy conditions in southern China (Lu et al, 2010;Wen et al, 2009;Zhou et al, 2009). In late January 2016, a strong cold event hit a large part of East Asia (Cheung et al, 2016;Geng et al, 2017;Song & Wu, 2017), setting the new lowest temperature record and causing the death of people in lower latitude East Asian regions (http://edition.cnn.com/2016/01/25/asia/asia-cold-weather-travel-disruption/index. html).…”
Section: Introductionmentioning
confidence: 99%